Relationship of suicide rates to economic variables in Europe: 2000–2011. (December 2014) - Fountoulakis, Konstantinos N.; Kawohl, Wolfram; Theodorakis, Pavlos N.; Kerkhof, Ad J. F. M.; Navickas, Alvydas; Höschl, Cyril; Lecic-Tosevski, Dusica; Sorel, Eliot; Rancans, Elmars; Palova, Eva; Juckel, Georg; Isacsson, Goran; et al.
Abstract : Background: It is unclear whether there is a direct link between economic crises and changes in suicide rates. Aims: The Lopez-Ibor Foundation launched an initiative to study the possible impact of the economic crisis on European suicide rates. Method: Data was gathered and analysed from 29 European countries and included the number of deaths by suicide in men and women, the unemployment rate, the gross domestic product (GDP) per capita, the annual economic growth rate and inflation. Results: There was a strong correlation between suicide rates and all economic indices except GPD per capita in men but only a correlation with unemployment in women. However, the increase in suicide rates occurred several months before the economic crisis emerged. Conclusions: Overall, this study confirms a general relationship between the economic environment and suicide rates; however, it does not support there being a clear causal relationship between the current economic crisis and an increase in the suicide rate.